Fish tanks - Anastacio, Alecx Samantha A. (Animo Repository, 2021)
Fish Tanks is a 20-minute short feature film about a man named Ed who is dealing with the inner turmoils of his separation from his long-term relationship. The event becomes a traumatic experience for Ed as it has affected his sense of stability and security. Simple tasks in his day job become a chore for him, which prohibits him from being an effective functioning human being. As Ed courses through his day working in the aquatic pet store with his cousin, he comes across a newly delivered Discus fish, a pet his former partner used to take care of. An unusual attachment forms between Ed and the Discus fish, which becomes a tool and path for the forgiveness of one’s self and redemption. This production unpacks peculiar and pivotal concepts on human-animal relationships and the implications of the attachment theory.Inspired by creative works that deal with human-animal relationships, the proponents wish to delve into the effectiveness of such attachment as a mechanism for coping during distressing and traumatic events. As a result, the narrative becomes an experiment of speculation on the possibility of pets that are too detached in terms of interaction and yet becoming the source of comfort and support to an individual. The fish becomes the subject of analysis due to the minute physical interaction between a human being and the aquatic animal. This unique approach allows Fish Tanks to create new discourses on the concepts that drive the production by materializing the idea of animals as secured attachment figures, support systems, and even a source of self-reflexive redemption.This short feature film will be shot in 1080p MP4 format.